Endoscopic laryngopharyngeal surgery for hypopharyngeal lesions. (July 2020) - Kishimoto, Yo; Tateya, Ichiro; Funakoshi, Makiko; Miyamoto, Shin-ichi; Muto, Manabu; Omori, Koichi
Highlights: Transoral surgeries are minimally invasive treatments for hypopharyngeal cancers. To achieve good hypopharyngeal exposure using a straight pharyngoscope is not easy. ELPS using a curved pharyngoscope is a feasible procedure for superficial cancers. Abstract: Objectives: Transoral approaches for laryngeal/pharyngeal malignancies have been widely accepted as minimally invasive treatment options; however, hypopharyngeal lesions treated by transoral surgery have rarely been reported due to the difficulties in visualizing the hypopharynx. Since 2010, we have treated superficial hypopharyngeal lesions with endoscopic laryngopharyngeal surgery (ELPS), and herein report the outcomes of this transoral procedure. Materials and Methods: One hundred and eighteen patients with superficial hypopharyngeal lesions were treated by ELPS from February 2010 to February 2017, and the clinical courses of the patients were reviewed. Results: Four females and 114 males (average: 65.6 y-o) were included in this study. Some patients had multiple lesions and a total of 154 superficial hypopharyngeal lesions (dysplasia: 29, Tis: 52, T1: 44, T2: 20, T3: 9) were treated with ELPS. Ten patients had only dysplasia and no carcinoma. Five patients presented with nodal metastases and 11 patients had simultaneous oropharyngeal lesions. In all cases, the hypopharynx was well visualized with sufficient working space, and no cases required a change in surgical approach. All post-operative complications were safely managed. In regard to the oncological outcomes, of the 108 patients with malignant lesions, the 3-year and 5-year overall survival (OS) rate was 93.6% and 85.5%, respectively. Conclusions: During ELPS, the hypopharynx was well visualized providing sufficient working space for the resection. The procedure was safe and feasible for superficial hypopharyngeal lesions and exhibited very good oncological outcomes. ELPS is thought to be a very effective surgical alternative for superficial hypopharyngeal lesions.